1933
DOI: 10.1139/cjr33-087
|View full text |Cite
|
Sign up to set email alerts
|

GELASINOSPORA, A NEW GENUS OF PYRENOMYCETES WITH PITTED SPORES

Abstract: Gelasinospora is a genus closely related to Sordaria, characterized by the foveolate sculpturing of the spore wall. At present it contains two species, as follows:—I. Gelasinospora tetrasperma, a coprophilous fungus which has been cultivated from spores collected in Manitoba and in Ontario.The species is described, together with illustrations of the chief characters, such as the four-spored condition of the ascus and the thickened ring bordering its apical perforation.Each normal-sized spore gives rise to a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

1936
1936
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 2 publications
0
17
1
Order By: Relevance
“…Dowding (1933) has reported that some spores of G. cerealis produce but one vesicle; this was not observed in any of our cultures.…”
Section: Methodscontrasting
confidence: 54%
See 1 more Smart Citation
“…Dowding (1933) has reported that some spores of G. cerealis produce but one vesicle; this was not observed in any of our cultures.…”
Section: Methodscontrasting
confidence: 54%
“…Gelasinospora, a genus of pyrenomycetes closely allied to Ne urospora and Fimetaria, was erected by Dowding (1933) on the basis of her studies on G. cerealis and G. tetraspernra, to include those two species.…”
Section: Introductionmentioning
confidence: 99%
“…Nothing is known genetically about G. tetrasperma beyond the fact that ascospores from its four-spored asci must be heterokaryotic for mating type, because [Dowding, 1933;Dodge, 1937, Campbell, 19371.…”
Section: Ascus Development In Gelasirwspora Tetraspermamentioning
confidence: 99%
“…The genera placed within this family mainly are differentiated by ascospore morphology and ornamentation. For instance, the genera Neurospora Shear & Dodge (1927) and Gelasinospora Dowding (1933) are morphologically comparable except the former produces ascospores with elevated longitudinal ridges (ribs) separated by depressed grooves (veins), and the latter produces ascospores with spherical or oval indentations (pits). Within these two genera, the patterns of ascospore ornamentation can vary significantly, and significant overlap may occur in morphological traits that are used to distinguish species.…”
Section: Introductionmentioning
confidence: 99%